Efficacy of transcranial magnetic stimulation treatment in reducing neuropsychiatric symptomatology after traumatic brain injury - Riccitelli, Gianna Carla; Borgonovo, Riccardo; Villa, Mariasole; Pravatà, Emanuele; Kaelin-Lang, Alain (Frontiers in Neurology, 2024)
Background Neuropsychiatric disorders are highly disabling in traumatic brain injury (TBI) patients, and psychopharmacological treatments often fail to adequately mitigate their detrimental effects. Repetitive transcranial magnetic stimulation (rTMS) is an emerging treatment in neurology and psychiatry, showing potential in treating psychiatric disorders. Objective This study investigates the efficacy of a novel, dual-site sequential rTMS protocol designed to treat neuropsychiatric symptoms in a TBI patient who was refractory to conventional treatments. Methods A 34-year-old woman with severe head trauma and complex psychopathology underwent 20 daily sessions of focal-coil rTMS, combining inhibitory stimulation (1 Hz) on the right dorsolateral prefrontal cortex (DLPFC) and excitatory (10 Hz) on the left DLPFC, guided by a neuronavigation system. Psychiatric and neurocognitive assessments were conducted at baseline and at 2, 4, and 8 weeks following the beginning of rTMS treatment. Results After 2 weeks of treatment, the patient showed decreased impulsivity and obsessive-compulsive symptoms, along with improvements in attention and processing speed. After 4 weeks, impulsivity further declined, though no other significant changes were noted. At 8 weeks, a persistent positive effect was observed, including enhanced positive emotions. Discussion These findings suggest that guided, alternating neurostimulation of the DLPFC may modulate activity within cortico-striato-thalamo-cortical circuits, providing a promising alternative for managing neuropsychiatric symptoms in TBI patients who are resistant to traditional treatments.